Employing High-Fidelity Simulation for the High-Risk, Low-Frequency Diagnosis and Management of Acute Radiation Syndrome (ARS) - Mel Ebeling; Andrew Bloom; Mary M. Boggiano; Dawn Taylor Peterson; Todd Peterson (Association of American Medical Colleges, 2023)
Introduction Acute radiation syndrome (ARS) is a high-risk, low-frequency diagnosis that can be fatal and is difficult to diagnose without an obvious history of ionizing radiation exposure. Methods Twenty-two emergency medicine residents and one pharmacy resident participated in an hour-long simulation session. To accommodate all learners, the simulation was conducted eight times over a block of scheduled time (two to four learners/session). Sessions included a prebriefing, pre/post questionnaires, the ARS case, and a debriefing. Learners evaluated and managed a 47-year-old male (manikin) with the hematopoietic and cutaneous subsyndromes of ARS who presented with hand pain/erythema/edema and underlying signs of infection 2 weeks after an unrecognized radiation exposure. Learners had to perform a history and physical, recognize/manage abnormal vitals, order/interpret labs, consult appropriate disciplines, and initiate supportive care. Results There was a mean reported increase in ability to recognize signs and symptoms of ARS (p < .001) and appropriately manage a patient with this condition (p = .03) even after controlling for baseline confidence in ability to make and manage uncommon diagnoses, respectively. Learners rated this simulation as a valuable learning experience, effective in teaching them how to diagnose and treat ARS, and one they would recommend to other health care professionals. Discussion This simulation aimed to teach the diagnosis and initial management of the hematopoietic and cutaneous subsyndromes of ARS. It should be used to increase awareness of the potential for ionizing radiation exposure under less obvious conditions and raise the index of suspicion for ARS in the undifferentiated patient.